2018
DOI: 10.1016/j.dr.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The influences of described and experienced information on adolescent risky decision making

Abstract: Adolescents are known to take more risks than adults, which can be harmful to their health and well-being. However, despite age differences in real-world risk taking, laboratory risk-taking paradigms often do not evince these developmental patterns. Recent findings in the literature suggest that this inconsistency may be due in part to differences between how adolescents process information about risk when it is described (e.g., in a description-based classroom intervention) versus when it is experienced (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 123 publications
(302 reference statements)
4
69
1
Order By: Relevance
“…Future longitudinal studies should further examine (a) how individual differences in NAcc sensitivity to rewards in adolescence relate to real‐life explorative behaviors and future achievements and (b) what motivates older adolescents and adults to obtain rewards and how this relates to NAcc reward responses. Importantly, future longitudinal studies should examine how rewards in different contexts, for example, when participants gain rewards for others or play a more complex reward task, affect neural reward mechanisms and behavior across adolescence and early adulthood (Rosenbaum, Venkatraman, Steinberg, & Chein, ). Together, our findings set the stage for future research into unique contributions of motivational factors for the neural underpinnings of explorative behaviors, which might ultimately help adolescents and young adults to become successful adults.…”
Section: Discussionmentioning
confidence: 99%
“…Future longitudinal studies should further examine (a) how individual differences in NAcc sensitivity to rewards in adolescence relate to real‐life explorative behaviors and future achievements and (b) what motivates older adolescents and adults to obtain rewards and how this relates to NAcc reward responses. Importantly, future longitudinal studies should examine how rewards in different contexts, for example, when participants gain rewards for others or play a more complex reward task, affect neural reward mechanisms and behavior across adolescence and early adulthood (Rosenbaum, Venkatraman, Steinberg, & Chein, ). Together, our findings set the stage for future research into unique contributions of motivational factors for the neural underpinnings of explorative behaviors, which might ultimately help adolescents and young adults to become successful adults.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental versions of these tasks typically present decision problems as 'wheels of fortune', where probabilities of each decision outcome are both written and visually depicted to aid younger participants in understanding the task [42]. Developmental patterns in decisions under risk are quite variable [7,8,14]. In studies that are limited to adolescent and adult age groups, over half do not report higher risk taking in adolescents [8].…”
Section: Decisions Under Riskmentioning
confidence: 99%
“…In contrast, a wealth of research has examined the development of decision making involving trade offs between gains and losses under risk (where the outcomes occur with some clearly specified probability; Boyer, 2006;Defoe, Dubas, Figner, & van Aken, 2015;Reyna, 2012). Moreover, developmental research has examined decisions in which information about probabilities is incomplete or ambiguous (e.g., Tymula et al, 2012), or in which both outcomes and their frequencies are uncertain and must be explored through experience (Rosenbaum, Venkatraman, Steinberg, & Chein, 2018;van den Bos & Hertwig, 2017). Further developmental studies have addressed how punishment and reward influences children's decisions in reinforcement learning (Costantini & Hoving, 1973;H€ ammerer, Li, M€ uller, & Lindenberger, 2010;van Duijvenvoorde, Zanolie, Rombouts, Raijmakers, & Crone, 2008).…”
Section: Motivational Sensitivity To Gains and Lossesmentioning
confidence: 99%
“…Cauffman et al reported that approach toward potential gains followed a curvilinear pattern across development, with sensitivity to positive feedback (to achieve gains) peaking during the adolescent years. Further research suggests that the attractiveness of gains in adolescence could be particularly prominent when decision problems involve active exploration (sampling of outcomes through experience; Rosenbaum et al, 2018) in heightened affective contexts (Figner, Mackinlay, Wilkening, & Weber, 2009).…”
Section: Motivational Sensitivity To Gains and Lossesmentioning
confidence: 99%
See 1 more Smart Citation